Analysis of Effective Administrative Management with the Application of Information Technology at SDN Pasar Minggu 01 - Ma'sum, Muhammad; Alim, Akhmad; Andriana, Nesia (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2024)
The role of information technology is also very important in improving time efficiency. SDN Pasar Minggu 01 can take advantage of the online time management system and schedule to optimize the use of learning and teaching time. However, the challenges faced in the application of information technology in schools are the readiness of infrastructure and technical skills of users. The purpose of this study is to find out the analysis of effective administrative management with the application of information technology in SDN Pasar Minggu 01. The research method that will be used in this study is quantitative. The research will collect data through a structured survey of stakeholders of SDN Pasar Minggu 01, which includes teachers, students, and administrative staff. The data will be analyzed using the Structural Equation Modeling (SEM) technique with the help of SmartPLS 3 software. The results of this study show that information technology and ease of budget management have a significant influence on administrative management performance. Information technology variables have a strong positive influence. The application of information technology at SDN Pasar Minggu 01 shows positive results, especially in management evaluation and administrative management performance, although there are challenges that need to be overcome in terms of ease of use of technology. This is evidenced by a strong positive relationship between information technology and administrative management performance (0.995).